2013
DOI: 10.1097/tp.0b013e318298dd65
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Pretransplantation Soluble BAFF Is Associated With an Increased Risk of Acute Antibody-Mediated Rejection

Abstract: These data raise the possibility that, in high immunologic risk patients undergoing Ai transplantation, the presence of elevated pretransplantation serum BAFF might identify those at increased risk of AMR. BAFF neutralization may be an interesting therapeutic strategy to explore in these patients, particularly because such agents are available and have already been used in the treatment of autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 30 publications
4
45
0
1
Order By: Relevance
“…Previous studies have demonstrated that an increased BAFF level directly correlates with the risk of alloantibody-mediated acute rejection in patients who received alemtuzumab induction and rapamycin monotherapy (50) as well as the patients who underwent antibody incompatible renal transplantation without depletional induction (51) . However, we demonstrate that an elevated BAFF level with a rapid repopulation of naïve but not memory B cells in the context of belatacept therapy supports this agent’s effectiveness in abrogating the production of donor specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that an increased BAFF level directly correlates with the risk of alloantibody-mediated acute rejection in patients who received alemtuzumab induction and rapamycin monotherapy (50) as well as the patients who underwent antibody incompatible renal transplantation without depletional induction (51) . However, we demonstrate that an elevated BAFF level with a rapid repopulation of naïve but not memory B cells in the context of belatacept therapy supports this agent’s effectiveness in abrogating the production of donor specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BAFF may promote naïve and transitional B cell maturation, possibly explaining the increase in AMR . Simultaneously, a high BAFF or BAFFR level is associated with a higher risk of Ab production in stable patients, Ab‐mediated rejection, and graft dysfunction . In humans, BAFF blockade using belimumab, a human monoclonal Ab against BAFF, has been shown to be effective in the treatment of systemic lupus erythematosus .…”
Section: Regulatory Functions Of B Cells In Transplantationmentioning
confidence: 99%
“…Disappointing results from clinical trials suggest that, on its own, BAFF antagonism is ineffective to durably reduce HLA antibody levels (82). However, given that higher BAFF levels are associated with greater sensitization to HLA (83,84) and AMR (85), it remains an intriguing therapeutic target in the quest for suppressors of HLA antibody production. Another BAFF antagonist, atacicept, reduced dnDSA production in a nonhuman primate model of renal transplantation (86), and belimumab, which showed efficacy in systemic lupus erythematosus (87), is being investigated to reduce pretransplant HLA allosensitization (NCT02500251, ClinicalTrials.gov).…”
Section: Complement Depositionmentioning
confidence: 99%